KARAKTERISTIK MORFOLOGI ESOFAGUS DAN LAMBUNG BANDIKUT (Echymipera kalubu) (Esophagus and Stomach Morphological Characteristic of Bandicoot Echymipera kalubu (Marsupialia: Peroryctidae)) - Ursula Paulawati Maker; Chairun Nisa; Srihadi Agungpriyono (Universitas Syiah Kuala, 2016)
The morphological characteristics of the stomach and esophagus of five adults bandicoot (Echymipera kalubu) with average 1.16±0.29 kg in body weight and 38.2±4.76 cm in body length were studied macroscopically, microscopically and histochemically. The bandicoot esophagus were found relatively long about one third of body length. The esophageal glands were identified along the esophagus and the number decreased gradually from cranial to caudal region. In addition of smooth muscle, skeletal muscles were also examined in the external muscle layer of esophagus up to the esophageal junction. The stomach of the E. Kalubu had short lesser curvature and three glandular regions of cardiac, fundic and pyloric glands were observed, respectively. The cardiac glands area was small and concentrated in the cranial part of the stomach. The fundic glands area occupied about half parts of the stomach. Mucous surface epithelial cells, mucous neck cells, parietal cells and chief cells were found in the entire fundic gland. The parietal cells were the most abundant cells in the major curvature distributed from the basal to neck area of the glands, but few in the minor curvature. Chief cells were mostly distributed in the basal gland. The pyloric glands region was observed in caudal part of the stomach. Staining with alcian blue-periodic acid Schift (AB-PAS) showed various distribution and intensity of neutral and acid mucopolysaccharides in the esophageal and stomach mucosa. High concentration of neutral and acid mucopolysaccharides were detected in esophageal and stomach glands with various concentration. Morphological characteristics of the esophagus and stomach were assumed to be related to the digestive processes in the gastrointestinal tract of bandicoot.